Hematological disorders: a commonly unrecognized cause of acute stroke. Issue 9 (1st September 2016) - Arboix, Adrià; Jiménez, Carme; Massons, Joan; Parra, Olga; Besses, Carles
ABSTRACT: Introduction : Hematological disorders account for about 1.3% of all causes of acute stroke. This systematized review presents updated information on the implications of this category of heterogeneous diseases as a cause of stroke. Areas covered : The most relevant aspects of the relationship between stroke and hematological disorders are reported. A high index of suspicion is needed in young stroke patients, patients with recurrent stroke of undetermined cause, and in patients with prior history of venous thrombosis to identify a potential hematological disorder as the definitive etiology of stroke Expert commentary : Stroke can be the presenting manifestation of a specific hematological disease or may appear as a complication in the course of hematological disorders. It is important to make a correct diagnosis of the underlying hematological disorder in order to treat stroke patients promptly and appropriately as well as to establish the optimal secondary prevention strategy for recurrent vascular cerebral disease.